2015
DOI: 10.1093/annonc/mdv329
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in stage III–IV adrenocortical carcinomas (ACC): an European Network for the Study of Adrenal Tumor (ENSAT) study

Abstract: The mENSAT classification and GRAS parameters (Grade, R status, Age and Symptoms) were found to best stratify the prognosis of patients with advanced ACC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
158
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(174 citation statements)
references
References 18 publications
10
158
4
2
Order By: Relevance
“…Retrospective data suggest that regional lymph node involvement in ACC has a negative impact on overall survival 67 and is frequently the cause of locoregional recurrence 85 -87 . As reported recently by Fassnacht et al 70 , and independently validated in North America in the Surveillance, Epidemiology, and End Results (SEER) registries 88 , patients with stage III tumours and positive lymph nodes can have a 10-year overall survival rate of up to 40 per cent after resection, although this finding has been challenged recently 89 -91 . It is not yet decided whether a modified ENSAT classification should consider node-positive ACC as stage IV disease 89 .…”
Section: Role Of Regional Lymphadenectomymentioning
confidence: 99%
“…Retrospective data suggest that regional lymph node involvement in ACC has a negative impact on overall survival 67 and is frequently the cause of locoregional recurrence 85 -87 . As reported recently by Fassnacht et al 70 , and independently validated in North America in the Surveillance, Epidemiology, and End Results (SEER) registries 88 , patients with stage III tumours and positive lymph nodes can have a 10-year overall survival rate of up to 40 per cent after resection, although this finding has been challenged recently 89 -91 . It is not yet decided whether a modified ENSAT classification should consider node-positive ACC as stage IV disease 89 .…”
Section: Role Of Regional Lymphadenectomymentioning
confidence: 99%
“…In adults, several studies have shown that older age is associated with decreased OS (5,6,8,9,26,30,32,39). Asare et al have even proposed a novel staging system, where stage I and stage II ACC were differentiated by age (≤55 years for stage I vs >55 years for stage II) and not by size, like it is done in the ENSAT-staging system (40).…”
Section: Agementioning
confidence: 99%
“…The Ki67 immunohistochemistry represents an alternative technique for assessing proliferation in ACC. Several studies have reported the prognostic value of Ki67 index in ACC (30,34,48,49,50,51,52). A large study in localized ACC identified Ki67 as the most powerful prognostic factor of DFS after complete surgery.…”
Section: Tumor Grade: From Mitoses To Ki67mentioning
confidence: 99%
“…Of 1523 eligible publications, nineteen (eighteen cohort studies, one RCT (1,4,7,17,18,19,20,21,22,23,24,25,26,27,28,29,30, 31, 32)) were included, representing a total of 3814 patients ( Fig. 1 for flow-chart of study inclusion).…”
Section: Study Inclusion and Study Characteristicsmentioning
confidence: 99%
“…Adrenocortical carcinoma (ACC) is a rare tumour with an incidence of less than 2 per million population. The prognosis remains poor with a 5-year overall survival of less than 50% and in metastatic disease less than 20% (1,2,3,4,5). Recurrences are frequent, even after apparent complete surgical resection.…”
Section: Introductionmentioning
confidence: 99%